2020
DOI: 10.1371/journal.pone.0244502
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating radiomic feature of pretreatment 18F-FDG PET improves survival stratification in patients with EGFR-mutated lung adenocarcinoma

Abstract: Background To investigate the survival prognostic value of the radiomic features of 18F-FDG PET in patients who had EGFR (epidermal growth factor receptor) mutated lung adenocarcinoma and received targeted TKI (tyrosine kinase inhibitor) treatment. Methods Fifty-one patients with stage III-IV lung adenocarcinoma and actionable EGFR mutation who received first-line TKI were retrospectively analyzed. All patients underwent pretreatment 18F-FDG PET/CT, and we calculated the PET-derived radiomic features. Cox pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Therefore, a more reliable prognostic stratification tool is an unmet need. The prognostic value of 18 F-FDG PET parameters derived from the primary tumor or the regional lymph node has been reported in patients with NSCLC [18][19][20]33,34]. However, the predictive power of combining the 18 F-FDG PET parameters from both primary tumor and metastatic nodes has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a more reliable prognostic stratification tool is an unmet need. The prognostic value of 18 F-FDG PET parameters derived from the primary tumor or the regional lymph node has been reported in patients with NSCLC [18][19][20]33,34]. However, the predictive power of combining the 18 F-FDG PET parameters from both primary tumor and metastatic nodes has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The validation process was executed using SPSS software (version 20.0; SPSS Inc., Chicago, IL, USA). The performance of our Cox regression models was assessed and compared with the AJCC staging system using Harrell's concordance index (c-index) and Kaplan-Meier curves (log-rank test) [19,31]. Different c-indices were compared using the "compareC" package installed on the R open-source statistical software version 3.4.2 (R Foundation, Vienna, Austria).…”
Section: Survival Model Validation and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that involve patients with advanced lung adenocarcinoma with epidermal growth factor receptor mutation who received tyrosine kinase inhibitor therapy revealed a shorter survival in patients with primary tumors with high entropy values. Additionally, they reported that entropy value is an independent predictor of treatment response and decreases after treatment ( 22 ). According to Hyun et al ( 23 ) lower entropy was independently associated with longer survival in patients with pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from the clinical profile and cancer staging system, which pictures the disease to a greater extent, texture analysis portrays more associations with aspects of tumor behavior. An increasing number of recent studies have demonstrated that tumor entropy is a robust predictor of survival in patients with lung cancer [ 25 , 26 , 27 , 28 , 29 ]. However, little is known about the comparison and potential combinations of hematologic inflammation biomarkers and tumor glycolytic heterogeneity in the current clinical setting.…”
Section: Introductionmentioning
confidence: 99%